Polarization doping technology towards high performance GaN-based heterostructure devices. (February 2019) - Wei, J; Ouyang, D F; Deng, S Y; Peng, F; Yang, C; Luo, X R
Abstract: GaN-based III-V heterostructure devices are promising candidates in future power electronic, microwave and optoelectronic devices, owing to their superior material properties. The development of polarization doping technology in GaN-based material has attracted extensive interests in the recent years, because it allows the graded AlGaN layers to realize high conductivity n/p type bulk doping without introducing donor/acceptor dopants, which would significantly improve the performances of the GaN-based heterostructure devices. This lecture contains two parts: an overview of polarization doping technology and novel polarization-doped GaN-based electron devices. The review of polarization doping technology mainly focuses on its mechanism in realizing the n/p type doping in graded AlGaN layer without impurity dopants, and its unique carrier characteristics induced by polarization doping. The novel polarization-doped GaN-based power devices include the diodes and field effect transistors, which exhibit better performances than the ones with impurity-doped.